The Impact of Loan Sharking on Victims Financial and Social lives: An online Survey of Victims Experiences in a Ghanaian context - Oti, Richard (Journal of Social Studies (JSS), 2024)
This study intends to contribute to the body of knowledge on loan sharking in Ghana and to provide policymakers, regulators, financial institutions, and community organisations with useful information by examining the impact of loan sharking on victims financial and social lives. The study utilised a survey research design to collect data from loan app victims. Snow ball sampling technique was used to collect data from loan app victims who responded to the survey. A total of 82 victims responded to the survey. A structured questionnaire was developed using Google Forms to collect data from participants. A descriptive statistical analysis was conducted to summarise the data collected from the survey. The study revealed that loan apps fulfil diverse needs, including providing quick and accessible funds, meeting basic necessities, circumventing social challenges, responding to familial rejection, capitalising on the influence of loan agents, facilitating entrepreneurial endeavours, and satisfying individual curiosity. The study further revealed a cycle of financial challenges, including difficulties in saving money, repeated borrowing, and significant financial burdens, suggesting a profound negative impact on participants' financial well-being. Furthermore, participants reported severe social consequences, including disgrace, social stigma, and damaged relationships.